Analisis Gaya Kepemimpinan Kepala Sekolah di SMK Negeri Kedawung - Qomariyah, Eva; Gayatri, Ratna; Udin, Tamsik (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2024)
Leadership in an organization, especially in the school world, has an important role in designing the organization's vision and mission and ensuring success and achievement of goals. The leadership style applied by the leader greatly influences the effectiveness of organizational management. This research uses a qualitative approach with descriptive analysis, with the principal of the Kedawung State Vocational School as the resource person. Leadership is a person's ability to influence other people to achieve organizational goals. There are various leadership styles, including: Authoritarian Leadership Style, Democratic Leadership Style, Free Leadership Style (Laissez-faire) and Visionary Leadership Style. The principal of Kedawung State Vocational School applies various leadership styles according to the situation, such as democratic and free for non-formal agendas, and authoritarian for a formal agenda. Research shows that each leadership style has advantages and disadvantages, and a good leader is one who can make decisions by considering the situation and the risks involved.